Histomorphogenesis of the Pharyngeal roof in Muscovy Ducks (Cairina moschata) - Fatma A. Madkour (South Valley University, 2020)
This study aimed to investigate the morphological characteristics of the pharyngeal roof of the developmental stages of Muscovy ducks from 1 to 60 days old. The statistical analysis revealed that the ratio of the pharyngeal roof to the total length of the oropharynx decreased with advancement of the age, which was recorded 19.44 % at one-day age and 15.19% at 60 days age, as well as the infundibular cleft was increased in length approximately by one and half at 15 days and three folds at 60 days when compared with that of one-day-old. SEM in one-day-old showed that, the fine pharyngeal papillae on each side of the infundibular slit, whereas, two types of the papillae at 15 days but numerous different size and shape caudally directed papillae at 60 days, some of them which were present at the pharyngoesophageal junction were in appearance of the nails of the carnivores. Numerous openings of the sphenopterygoid salivary glands were scattered between these papillae, which were observed in older ages (60 days old) by few numbers in the shallow groove at the caudal commissure of the infundibular slit. The edges of the infundibular cleft were smooth in all developmental stages except at 60 days old where few, fine and caudally directed papillae were recognized. Histologically, the sphenopterygoid salivary glands were compound tubulo-alveolar mucous secretory glands which was surrounded by lymphatic aggregation in older ages. In all examined ages, lymphatic accumulation could be observed in the infundibular cavity which was surrounding the intraepithelial mucous glands.